Hyperkeratosis of vertebral apophysis. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
Level with the apophyses of the lowest toracic vertebrae you can not exceptionally observe a brownish pigmentation. It is expression of a trivial callosity. However, it is sometimes the reason of examination in the adolescent.